PENGARUH MEDIA EDUKASI APLIKASI BERBASIS MOBILE ANDROID TERHADAP PENGETAHUAN SISWA SMP TENTANG PENCEGAHAN SEKS PRANIKAH DI KOTA BANDUNG (Jurnal Kesehatan Siliwangi, 2023)
Backgroud. According to the results of the 2017 SDKI, female adolescents (81%) and male adolescents (84%) have been in a relationship. In the same survey, 59% of women and 74% of men. Losses that can occur due to premarital sex are unwanted pregnancies and unsafe abortions (SDKI, 2017). West Java is ranked first for having an adverse event rate (22.8%) and an attempt to terminate a pregnancy (18.2%). In the city of Bandung, as many as 8.81%, or as many as 300 thousand teenagers, are married at the age of less than 16 years. Therefore, it is necessary to provide health education about the importance of preventing premarital sex in adolescents through android-based mobile application media. Objective: to determine the effect of an Android-based mobile application on students' knowledge of prevention of premarital sex at SMP Yaqin Bandung. Methods: quasy-experimental research design with one group pretest-posttest without control. The sample of this study used a total sampling of 72 respondents came from 8th grade students. Data collection using the questionnaire instrument via google form and measured by a knowledge scale.The media is developed using the 4D model, with result are worthy bith media and materials experts. Data analysis used the. Results: The average score of the respondent's knowledge before being given an Android-based mobile application media was 63.72. The average knowledge of respondents after being given an Android-based mobile application media was 82.55. The percentage increase in knowledge is 29%. The p value of respondents' knowledge before and after being given the media was (p = 0.000). Conclusion: the influence of android-based mobile application on knowledge of prevention of premarital sex in grade 8 student at SMP Yaqin Bandung.